HUBUNGAN USIA DAN JENIS KELAMIN DENGAN KEJADIAN KANKER DI RS PKU MUHAMMADIYAH YOGYAKARTA - Nur Afni Sharfina; Ratna Indriawati (Journal of Innovation Research and Knowledge, 2021)
Background: The global incidence of cancer has increased in the previous three years. According to WHO estimations from 2018, Indonesia is the 23rd nation in Asia with the largest number of cancer patients. Cancer is a disease in which aberrant cells spread uncontrollably and can result in death. Until today, the cause of cancer has remained unknown. A number of variables have been discovered to contribute to a rise in cancer prevalence. Age and gender are two of these variables. Purpose : The purpose of this research is to see if there is a link between age, gender and cancer incidence in the PKU Muhammadiyah Hospital in Yogyakarta. Method: The research is analytic and uses a cross-sectional method. The research included 142 cancer patients at PKU Muhammadiyah Hospital who were currently receiving therapy, and 105 samples were collected. The chi-square test was used to do bivariate analysis.Result: The majority of cancer patients at PKU Muhammadiyah Yogayakarta Hospital were between the ages of 40 and 49. (50.5%). Female respondent, with a total of 67 persons, dominated the number of cancer patients (63.8 percent).Conclusion: There is a correlation between gender and age with the incidence of cancer at PKU Muhammadiyah Hospital Yogyakarta